1993
DOI: 10.2307/3431900
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Polychlorinated Biphenyls to the Aryl Hydrocarbon Receptor

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…These results are consistent with research previously performed by Kafafi et al (27) on the entire congeneric series of chlorinated biphenyls. In this study, the authors presented a thermodynamic model based on lipophilic, electronic, and entropic characteristics for calculating the dissociation constants of ligand-receptor complexes.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with research previously performed by Kafafi et al (27) on the entire congeneric series of chlorinated biphenyls. In this study, the authors presented a thermodynamic model based on lipophilic, electronic, and entropic characteristics for calculating the dissociation constants of ligand-receptor complexes.…”
Section: Discussionsupporting
confidence: 94%
“…A significant amount of information suggests that the AhR can be bound and/or activated by chemicals for which the structural and physicochemical properties deviate from the defined structural requirements for AhR ligands [12, 13, 27, 31]. In line with this, our thorough computational study has shown that carbaryl preferentially takes a nonplanar conformation (CAR‐I).…”
Section: Discussionmentioning
confidence: 73%
“…The importance of planarity for AhR binding and CYP1A induction was exemplified by PCBs, from which congeners with para ‐ or meta ‐substitution, which can easily take a coplanar conformation, are potent CYP1A inducers, but ortho ‐substituted congeners, for which a coplanar conformation is energetically unfavorable, are weak or noninducers of CYP1A [9]. However, this statement has been questioned by several authors who determined, using computational studies, that some PCBs traditionally considered as AhR ligands are not coplanar molecules [12, 13]. In addition, it was found that some electrostatic properties (i.e., the dipole and quadrupole moments [14] and the electrostatic potential) were significant in rationalizing the effect on AhR.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that planar CBs are enriched in the aquatic food chain in comparison to nonplanar CBs, because planar CBs have a higher lipophilicity than similar nonplanar CBs [36]. Indeed, the depuration rate constants of planar CBs from mussels and oysters are lower than for other congeners with the same number of chlorine atoms [37,38].…”
Section: Resultsmentioning
confidence: 99%